The Development of Self-Preservation - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2002)
The problem of human self-preservation in this eternally changing world is barely researched in the pedagogical literature. In this article, we seek to ensure content analysis of self-preservation, and to present some tasks and methods of development. The main concepts are: reaction, causing, say, taking the sensation, rejecting the challenge, reluctance of the response, selection, adaptation.
Keywords: Education; self-preservation; taking the sensation; rejecting the challenge; reluctance of the response; selection; adaptation.